Pengaruh Ratio Jantan Dan Betina Terhadap Fertilitas Dan Daya Tetas Telur Ayam Kampung - Maya Salamony; N Souktta; Simon Petrus Telussa; Gardis Andari (Faculty of Agriculture, Musamus University, 2019)
Abstract. Chicken livestock development can increase rapidly, if the supply of seeds can run well, followed by regular management, feeding, breeding and disease prevention. So far the exact ratio of males and females is unknown, especially by rural communities so hatching failures often occur. This study aims to determine the ratio of male and female to fertility, egg hatchability and egg hatching weight of native chicken. The experiment was carried out using 8 males and 60 females as elders, and divided into four treatments and two replications with the ratio of males and females, A (1:5); B (1:7); C (1:9); D (1:11), Continued hatching of 120 eggs with 15 treatments each. Data were analyzed using Analysis of Variance in Completely Randomized Design (CRD). If between treatments showed significant differences, it was continued with the Honestly Significant Difference test (BNJ). The results showed that the highest fertility was in group B (96.66) and the lowest in group D (56.66). The highest hatchability was in group B (96.66) and the lowest in group D (56.66). The highest hatching weights were in group B (23.18) and the lowest in group D (21.33). This study can be concluded that the ferlititas, hatchability of eggs is much better in group B and the hatching weight of native chicken eggs is much better in group B.